Reclamation of the Narrative for the Silenced Voice in Margaret Atwood’s The Penelopiad - G.C., Saroj (Literary Studies, 2021)
This article analyzes Margaret Atwood’s The Penelopiad, a rewriting of Homeric epic, The Odyssey. Atwood rewrites the story — the saga of gallantry and triumphalism of Odysseus, with narrative shift that brings postmodern irony and parody, self-reflexivity and metafiction, and intertextuality and paratextuality into play. The article tries explore if Atwood’s shifting of narrative orientation of the Homeric epic yields any different and substantial reception and interpretation of the epic in the recent context.Moreover, I demonstrate how Atwood’s reconstruction and subsequently the empowerment of the minor characters unfolds the incompatibilities and discrepancies the official version of Homer’s epic, and brings the marginal voice to the front by granting a variety of narrative access.I argue, giving subject positions to silent agents and using various genres of expression, for instance, history and myth, Atwood, through the deployment of an autodiegetic narrative, brings together gender, genre and language in such a way that results in a decisive shift in conceptualizing the narrative structure for the marginal voice and agency female characters. The article concludes that why rereading of classical and canonical text is crucial to bring the marginals’ claim to a subject position, and produce a different language and literature that allows space for expression subjectivity of characters on the margins